Ex Vivo Assessment of Sentinel Lymph Nodes in Breast Cancer Using Shear Wave Elastography. (29th December 2015) - Kilic, Fahrettin; Velidedeoglu, Mehmet; Ozturk, Tulin; Kandemirli, Sedat Giray; Dikici, Atilla Suleyman; Er, Mehmet Emin; Aydogan, Fatih; Kantarci, Fatih; Yilmaz, Mehmet Halit
Abstract : Objectives: Axillary lymph node status is one of the important prognostic factors in early‐stage breast cancer. Despite the combined use of sonography, fine‐needle aspiration, and sentinel lymph node (SLN) dissection, there is a gap between the potential effectiveness of those techniques and current success to determine the axillary lymph node status. The main aim of this study was to evaluate the baseline accuracy of shear wave elastography for differentiation of benign versus malignant SLNs in an ex vivo artifact‐free environment. Methods: Thirty patients with breast cancer scheduled for SLN dissection were enrolled prospectively after informed consent and Institutional Review Board approval were obtained. After dissection, lymph nodes were embedded in ultrasound gel and examined with grayscale sonography and shear wave elastography. Findings were compared to histopathologic results. Results: A total of 64 SLNs obtained from the 30 patients were evaluated. Twelve of them (18.8%) were metastatic, and 52 (81.2%) were benign. The mean cortical thickness (benign versus metastatic, 1.6 versus 4.4 mm), short‐axis length (4.63 versus 7.50 mm), cortical stiffness (10.7 versus 25.5 kPa), and hilar stiffness (7.5 versus 11.3 kPa) were statistically higher in metastatic lymph nodes ( P ≤ .02). Area under the receiver operator characteristic curve values for these variables were 0.814, 0.768, 0.786, and 0.759, respectively. Cortical thickness was found to have the highest diagnostic performance, followed by cortical stiffness. Conclusions: Shear wave elastography can be used with grayscale sonography for evaluation of cases to decide on needle biopsy sampling. However, it cannot be used as a replacement for fine‐needle aspiration or SLN dissection.